Meditative Movement for Depression and Anxiety - Payne, Peter; Crane-Godreau, Mardi A. (Frontiers in Psychiatry, 2013)
This review focuses on Meditative Movement (MM) and its effects on anxiety, depression and other affective states. MM is a term identifying forms of exercise that use movement in conjunction with meditative attention to body sensations, including proprioception, interoception and kinesthesis. MM includes the traditional Chinese methods of Qigong (Chi Kung) and Taijiquan (Tai Chi), some forms of Yoga and other Asian practices, as well as Western Somatic practices; however this review focuses primarily on Qigong and Taijiquan. We clarify the differences between MM and conventional exercise, present descriptions of several of the key methodologies of MM, and suggest how research into these practices may be approached in a systematic way. We also present evidence for possible mechanisms of the effects of MM on affective states, including the roles of posture, rhythm, coherent breathing, and the involvement of specific cortical and subcortical structures. We survey research outcomes summarized in reviews published since 2007. Results suggest that MM may be at least as effective as conventional exercise or other interventions in ameliorating anxiety and depression; however, study quality is generally poor and there are many confounding factors. This makes it difficult to draw definitive conclusions at this time. We suggest, however, that more research is warranted, and we offer specific suggestions for ensuring high-quality and productive future studies.